Collective scaffolding in second language learning: a window into an online business writing class / Shanthi Nadarajan - Nadarajan, Shanthi (Universiti Teknologi MARA Cawangan Kedah, 2018)
This paper explores the use of online teaching of negotiation and writing skills to second language learners in an undergraduate workplace English course. Using the case method as approach to get learners to work on authentic workplace issues through meetings and face to face sessions, the analysis of their embedded online discussions and comments for two writing tasks (online and face to face) revealed that while meaning negotiation, error corrections and technical actions did occur, social talk and content management happened to predominate online discussions. Further analysis revealed that the relationship among different types of online writings and subsequent writings and revision though complex where highly dependent on group makeup, proficiency level and learner motivation. Student reflections suggest that while being interested in online activities alone does not guarantee quality writing, the ability to see words in print enabled learners to understand the meeting process and this helped them use reported speech more efficiently. Writing instructors may need to proactively intervene from time to time to raise awareness on the required form, model, scaffold, and support revision activity to ensure learning takes place.